Gray matter volume of cerebellum associated with idiopathic normal pressure hydrocephalus: A cross-sectional analysis - Lv, Minrui; Yang, Xiaolin; Zhou, Xi; Chen, Jiakuan; Wei, Haihua; Du, Duanming; Lin, Hai; Xia, Jun (Frontiers in Neurology, 2022)
The cause of idiopathic normal pressure hydrocephalus's (iNPH) clinical symptoms remains unclear. The cerebral cortex is the center of the brain and provides a structural basis for complex perception and motor function. This study aimed to explore the relationship between changes in cerebral cortex volume and clinical symptoms in patients with iNPH. This study included 21 iNPH patients and 20 normal aging (NA) controls. Voxel-based morphometry statistical results showed that, compared with NA, the gray matter volumes of patients with iNPH in the bilateral temporal lobe, bilateral hippocampus, bilateral thalamus, bilateral insula, left amygdala, right lenticular nucleus, right putamen, and cerebellum decreased, while the volumes of gray matter in the bilateral paracentral lobules, precuneus, bilateral supplementary motor area, medial side of the left cerebral hemisphere, and median cingulate and paracingulate gyri increased. Correlation analysis among the volumes of white matter and gray matter in the cerebrum and cerebellum and the iNPH grading scale (iNPHGS) revealed that the volume of white matter was negatively correlated with the iNPHGS (P < 0.05), while the gray matter volumes of cerebellar area 6 and area 8 were negatively correlated with the clinical symptoms of iNPH (P < 0.05). The volume of gray matter in the cerebellar vermis was negatively correlated with gait, and the gray matter volume of cerebellar area 6 was negatively correlated with cognition. Our findings suggest that the cerebellum also plays an important role in the pathogenesis of iNPH, potentially highlighting new research avenues for iNPH.